A Retrospective Cohort Study of Traumatic Root Fractures in Primary Dentition: Can Splinting Type Improve Therapeutic Outcomes? - Martina Salvatorina Murgia; Nicoletta Zerman; Stefano Cubeddu; Laura Carboni; Enrico Spinas (Applied Sciences, 2023)
(1) Introduction: Deciduous traumatic dental injuries pose a serious global health concern. Root fractures show an incidence rate of approximately 2%; however, the literature is limited regarding the appropriate treatment and prognosis of affected teeth. This retrospective study aims to analyze the long-term outcomes of orthodontic splinting using brackets compared with composite resin-only splinting in two homogeneous samples affected by root fractures. The study also examines the onset and patterns of root resorption. (2) Methods: The first group included 25 patients with 27 deciduous upper incisors affected by root fracture; Group 2 consisted of 35 patients with 38 root fractures of maxillary deciduous teeth. The categorical data for both groups were analyzed using the chi-squared homogeneity test. Age groups were compared using the Mann–Whitney U test; p < 0.005 was considered statistically significant. (3) Results: In both groups, the male gender predominated similarly. In Group 1, early decidual loss occurred in 16% of cases, whereas in Group 2 it occurred in 51% of cases. Pulp canal obliteration was observed in 68% of deciduous teeth in Group 1, compared with 30% in Group 2. No complications affecting permanent teeth were noted in Group 1; in Group 2, 29% developed enamel dysplasia and 26% experienced delayed eruption, with statistically significant differences in these proportions. Apical fragment resorption was observed in 92% of cases in Group 1 and 30% in Group 2. (4) Conclusions: The treatment of deciduous tooth root fractures using orthodontic splints can yield significant benefits, such as reduction of early tooth loss. Furthermore, the study confirms that early resorption of the distal fragment of fractured roots is a common physiological phenomenon in primary teeth and typically occurs within a year following trauma.